The Efficiency of e-Services in Mexico: a Multidimensional Perspective – Federal Driver's License Digitization Case Study - Carrera Mora, Oscar yahevh; Ovando Chico, María Catalina (Law, State and Telecommunications Review, 2022)
[Purpose] The purpose of this study is to determine the benefits of e-services, both for a government agency and for citizens in terms of efficiency, derived from the digitalization of one of its processes. [Methodology/Approach/Design] A case study is presented of a project developed and implemented in 2021 in Mexico at the federal level by the Ministry of Communications and Transportation (SCT), which consisted of the digitalization of the process of issuance and/or revalidation of the Federal Driver's License. The first two months of operation are taken as a reference to determine the effects that this digital platform has had on economic, technical, and social efficiency. Analyzing the number of requests handled, costs for both the government and the citizen compared to the printed license and its processes. [Findings] Its theoretical basis is an analysis of efficiency based on a multidimensional notion of the concept, which is important since it analyzes improvement scenarios from the government's and citizens' points of view. The above allows this study to determine the benefits of electronic government services, both for a government agency and for citizens in terms of efficiency. [Practical Implications] The benefits that the Federal Digital License has represented in terms of cost reduction, process improvement, and increased citizen service the Federal Digital License have been demonstrated to these two actors. [Originality] The difference with the contributions of other studies lies in the object of study, which is the Federal Driver's License system, a case that has not been studied due to its recent implementation. This opens the door to future research, where not only quantitative data expressed in numerical terms can be analyzed, but also user satisfaction can be directly evaluated qualitatively.